Synthesis of Silver Abietate as an Antibacterial Agent for Textile Applications - A. Yıldız; M. Değirmencioğlu (Bioinorganic Chemistry and Applications)
This study explored the potential use of new silver abietate obtained from abietic acid as an antibacterial agent for textile applications. Synthesis, structure, and antibacterial studies of silver abietate compound are reported. Silver complex was obtained reacting abietic acid with silver. The new compounds were characterized by 1H NMR, 13C NMR, DEPT, IR, UV, and ESI-MS techniques which support the proposed structures. The new Ag abietate complex has no environmental hazard, its antibacterial activities were evaluated after being applied to cotton fabric by padding process according to the JIS L 1902-2008 agar diffusion test method and against three Gram-negative and three Gram-positive bacteria, respectively. Stability of antibacterial effect after repeated washings (3, 5, 10, and 20) was also tested which indicated that the synthesized silver abietate compound could be used as a new antibacterial agent in textile industry. In this way, the compound has been synthesized the first time in the literature and the applications have been investigated.